Analysis of the peri-implant soft tissues in contact with zirconia abutments: an evidence-based literature review - Medeiros, Rodrigo Antonio de [UNESP]; Vechiato-Filho, Aljomar José [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Santos, Daniela Micheline dos [UNESP]; Goiato, Marcelo Coelho [UNESP] (Jaypee Brothers Medical Publishing, 2013)
The aim of this study is to evaluate through a literature review, the soft tissue response in contact with zirconia abutments, including case reports comparing prosthetics rehabilitations with zirconia and titanium abutments upto 3 years of follow-up as well as the factors that should be considered on implant's abutment selection. Metallic abutments can provide grayish color when in contact with thin soft tissues which may lead the implant prosthetic treatment to failure. In this context, the abutments of zirconia stand out because there is an excellent linking between esthetics and the health of peri-implant soft tissues. A consult of the published researches was made on the PubMed database from 2000 to September 2012. The including criteria were: literature reviews, clinical studies and case reports in English that focused on the response of the soft tissue in contact with zirconia implant abutments. The studies that were not in English and did not match the tackled issue were excluded. A total of 32 articles were found. According to the search strategy, just 16 articles were selected for this review. Three studies affirmed that zirconia abutments have an excellent soft tissue response; one study showed increased gingival recession with zirconia abutments and nine studies do not stand out any difference on biological behavior between titanium and zirconia abutments. Three studies affirmed that zirconia abutments provide natural gingival appearance, anatomic contour and greater esthetics. The use of zirconia abutments is recommended for anterior regions because of their greater optical properties and esthetic results and more studies should be performed and analyzed longitudinally regarding their biological response. The zirconia abutments have been established to be essential in order to achieve great esthetic results in cases of thin peri-implant soft tissues and in regions where the three-dimensional placement of implants is more superficial.
Keywords: Dental implants; Gingiva; Esthetics; Review